Exploring the 31P chemical shift behavior of high-energy phosphates at 7 T in patients with glioma - Franke, Vanessa L.; Kroh, Florian; Seng, Bela; Platek, Justyna; Weckesser, Nina; Schlemmer, Heinz-Peter; Ladd, Mark E.; Bachert, Peter; Paech, Daniel; Korzowski, Andreas (Frontiers in Neuroscience, 2025)
IntroductionThe characterization of tumor microenvironment in vivo can be supported by 31P MRSI, a non-invasive technique that enables the determination of intracellular pH and magnesium ion concentration, among other parameters. However, it remains unclear from recent studies whether imaging biomarkers, like the intracellular pH value (as determined conventionally via the chemical shift separation between inorganic phosphate (Pi) and phosphocreatine), are correlated with different glioma subtypes. Therefore, this study aimed to explore the behavior of multiple chemical shifts, specifically those of Pi and adenosine triphosphate (ATP), to approach a more detailed characterization of glioma tissues.MethodsA retrospective analysis on 31P MRSI datasets from 11 patients with newly diagnosed glioma acquired at 7 T prior to any treatment was conducted. Mean values of the quantified chemical shifts of Pi, γ-, α- and β-ATP across different regions-of-interest were determined for each patient separately. The mean chemical shifts were compared for different tumor sub-compartments and for different IDH mutation status.ResultsIn high-grade gliomas, significant differences in chemical shifts were observed between tumor and healthy tissue. In low-grade glioma, smaller differences were found for the chemical shifts of Pi, γ- and α-ATP than in the high-grade glioma. The latter pattern was not observed for β-ATP resonances, where the mean chemical shift across the tumor was comparably high between low-grade and high-grade glioma. In patients with IDH-wildtype, slightly stronger shifts of Pi and γ-ATP peaks were observed than for patients with IDH-mutant. No differences between IDH-wildtype and IDH-mutant were observed for the chemical shifts of α- and β-ATP.DiscussionThese findings suggest a potential benefit of a joint evaluation of Pi and ATP chemical shifts for possible discrimination of different glioma subtypes. Using the complementary information of multiple 31P chemical shifts could improve the characterization of tumor tissue and provide new insights beyond current knowledge.